Can Our Schools Help Us Preserve Democracy? Special Challenges at a Time of Shifting Norms - Levinson, Meira (The Hastings Center report, 2021)
Civic education that prepares students for principled civic participation is vital to democracy. Schools face significant challenges, however, as they attempt to educate for democracy in a democracy in crisis. Parents, educators, and policy-makers disagree about what America's civic future should look like, and hence about what schools should teach. Likewise, hyperpartisanship, mutual mistrust, and the breakdown of democratic norms are perverting the kinds of civic relationships and values that schools want to model and achieve. Nonetheless, there is strong evidence that young people want to be civically engaged and are hungry for more and better civic learning opportunities. Reviving the civic mission of schools is thus a win-win-win. Adults want it, youth want it, and democracy needs it. We propose three means by which educators and the public can reconstruct our common purpose and achieve civic innovation to help democracy in crisis: support action civics, strengthen youth leadership outside the classroom, and engage both students and adults with “hard history” and contemporary controversies.